Perturbative approximations to single and double spin flip equation of motion coupled cluster singles doubles methods - Dutta, Achintya Kumar; Pal, Sourav; Ghosh, Debashree (Journal of Chemical Physics, 2013)
Spin flip equation of motion coupled cluster (EOM-SF-CC) can correctly treat situations involving electronic degeneracies or near degeneracies, e. g., bond breaking, di- and tri-radicals, etc. However, for large systems EOM-SF-CC (even in single and double excitations) is computationally prohibitively expensive. Therefore, earlier approximations to EOM-SF-CC methods such as spin flip configuration interaction singles with perturbative doubles (SF-CIS(D)) have been proposed. In this work, we present a new perturbative approximation to EOM-SF-CC, which has been found to be more accurate than SF-CIS(D). The capabilities, advantages, and timings of the new approach have been demonstrated considering the singlet-triplet gaps in di- and triradicals as well as bond breaking examples. The method is extended to double spin flip EOM-CC and its capabilities have been tested. (C) 2013 AIP Publishing LLC.